Mapping Learning Achievements and Teaching Materials for Islamic Religious Education and Character Elements of the History of Islamic Civilization in the Independent Curriculum - Salsabila, Silvia; Fakhruddin, Agus; Abdillah, Hilman Taufik (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
The curriculum is constantly being improved until in 2022 the government introduces the Independent Curriculum. However, in its implementation, this curriculum still faces various challenges, including difficulties for teachers in understanding learning achievements and applying them in teaching materials. This study aims to analyze and ensure that the learning achievements and teaching materials of Religious Education and Character, especially the elements of the History of Islamic Civilization, are by the level of students' thinking ability. The research method used is the study of learning achievement documents and Religious Education and Character textbooks from grades I to XII version of the Independent Curriculum. The results of the study provide findings in the form of mapping learning achievements and teaching materials of Religious Education and Character of the History of Islamic Civilization based on the cognitive, affective, and psychomotor domains. Keywords: Religious Education and Character, Mapping, History of Islamic Civilization